Institutional Interest in Corporate Responsibility: Portfolio Evidence and Ethical Explanation - Cox, Paul; Wicks, Patricia Gayá (2011)
This study examines the extent to which corporate responsibility influences the demand for shares by institutions. The study follows Bushee (Account Rev 73(3):305–333, 1998) in categorising institutions as dedicated or transient. The demand for shares is organised according to three factors: a long-term factor, corporate responsibility; a short-term factor, market liquidity; and a time-independent factor, portfolio theory. The rank and importance of the factors for the different types of institutional investor are analysed. For one of two types of dedicated institution, corporate responsibility is as important as portfolio theory in influencing the demand for shares. For all dedicated institutions, corporate responsibility influences the demand for shares more than market liquidity. For two of the three types of transient institution, market liquidity is the most important factor in share selection. For all transient institutions, the least important factor is corporate responsibility. Findings suggest that corporate responsibility positively and significantly influences the demand for shares by dedicated institutions. The discussion considers the extent to which these trends are constitutive of significant shifts in ethicality within the context of institutional investment. Looking at this from within a highly institutionalised Anglo market model, dedicated institutions’ commitment to broader and longer-term concerns could be interpreted as a small but significant step towards a more axiologically informed ethical business practice. Such a form of engagement calls for sensitive attention to a fuller range of features deemed to be relevant to investment decisions, as opposed to more narrow reliance on legislation, codes of practice and fiduciary principles.
Keywords: Business Ethics; institutional investment; Corporate Responsibility; share ownership